Adjuvant electroconvulsive therapy with antipsychotics is associated with improvement in auditory mismatch negativity in schizophrenia. (May 2022) - Liu, Yi; Jia, Li-na; Wu, Han; Jiang, Wei; Wang, Qian; Wang, Dan; Xiong, Yan-bing; Ren, Yan-ping; Ma, Xin; Tang, Yi-lang
Highlights: Thirty-seven patients with schizophrenia received 8 bifrontal adjuvant ECT treatments with atypical antipsychotics. The frequency and duration MMN of auditory stimuli were measured before and after ECT treatments. The Positive and Negative Syndrome Scale was used to assess clinical symptoms. Cognitive function was assessed using the MATRICS Consensus Cognitive Battery. At baseline, compared with healthy controls, patients with schizophrenia had a significantly lower amplitude of both MMN-F and MMN-D and significantly longer MMN-D latency. Compared with baseline, the amplitude increased significantly and the latency shortened significantly in patients with schizophrenia, both in frequency and duration MMN after 8 ECT treatments. The improvement of cognitive function was significantly correlated with the change of MMN latency. There was a significant correlation between the change of MMN amplitude and the change of general psychopathological subscale of PANSS. MMN may be a biomarker of the effects of ECT on cognitive function in patients with schizophrenia.